2021
DOI: 10.1021/acs.inorgchem.0c03599
|View full text |Cite
|
Sign up to set email alerts
|

Corrole-Substituted Fluorescent Heme Proteins

Abstract: Although fluorescent proteins have been utilized for a variety of biological applications, they have several optical limitations, namely weak red and near-infrared emission and exceptionally broad (>200 nm) emission profiles. The photophysical properties of fluorescent proteins can be enhanced through the incorporation of novel cofactors with the desired properties into a stable protein scaffold. To this end, a fluorescent phosphorus corrole that is structurally similar to the native heme cofactor is incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 109 publications
0
36
0
1
Order By: Relevance
“…P-1 does not bind histidine, and DFT calculations confirm that imidazole binding is destabilising. 28 The H102G variant exhibited impaired corrole incorporation (59% relative to WT H-NOX). To rescue corrole binding with a hydrogen bonding partner, H102S was prepared.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…P-1 does not bind histidine, and DFT calculations confirm that imidazole binding is destabilising. 28 The H102G variant exhibited impaired corrole incorporation (59% relative to WT H-NOX). To rescue corrole binding with a hydrogen bonding partner, H102S was prepared.…”
Section: Resultsmentioning
confidence: 97%
“…S19b, ESI † ), which likely precludes this contact from forming in the variant. It was previously demonstrated that P-1 incorporation decreases with increasing pH, 28 suggesting that protonation of this residue occurs at lower pH to enhance corrole binding. Moreover, protonation of H102 explains why the WT protein and H102 variants exhibit the same emission intensity.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…100). 281 The binding of the corrole in the heme pocket of the protein was confirmed by emission and absorption spectroscopy, demonstrating the proof-of-principle and the possibility to further develop new fluorescent proteins. Interestingly, these corrole-substituted heme proteins were shown to exhibit more intense fluorescence (in a narrower spectral profile) than traditional fluorescent proteins that emit in the same spectral window.…”
Section: Fluorescent Heme Proteinsmentioning
confidence: 83%
“…Interestingly, these corrole-substituted heme proteins were shown to exhibit more intense fluorescence (in a narrower spectral profile) than traditional fluorescent proteins that emit in the same spectral window. 281 It was shown also that the corrole emission was enhanced in the HasA conjugate but was quenched in the H-NOX.…”
Section: Fluorescent Heme Proteinsmentioning
confidence: 98%